Effect of impregnation sequence of Pd/Ce/γ-Al2O3 sorbents on Hg0 removal from coal derived fuel gas. (June 2020) - Huo, Qihuang; Yue, Caixia; Wang, Yahui; Han, Lina; Wang, Jiancheng; Chen, Shuai; Bao, Weiren; Chang, Liping; Xie, Kechang
Abstract: This study attempted to investigate the effect of impregnation sequence of the Pd/Ce/ γ -Al2 O3 sorbents on Hg 0 removal. To this end, five kinds of sorbents were prepared and tested in simulated coal derived fuel gas (N2 –H2 –CO–H2 S–Hg), including Pd/ γ -Al2 O3, Ce/ γ -Al2 O3 and three kinds of Pd-based sorbents with Ce impregnation on γ -Al2 O3 substrate. The tests were conducted at 250 and 300 °C respectively. According to the results, bimetallic Ce–Pd/ γ -Al2 O3 sorbent prepared by simultaneously impregnating Pd and Ce showed much higher and more stable removal efficiency of Hg 0 than the other three kinds of sorbents. The Hg 0 removal efficiency of Ce–Pd/ γ -Al2 O3 sorbent reached above 98% within 480 min at 250 °C and 91% within 200 min at 300 °C. Characterization results indicated that the sorbent Ce–Pd/ γ -Al2 O3 prepared by the co-impregnation method had bigger specific surface area (216.6 m 2 /g) than the other three kinds of Pd-based sorbents. The content Pd and Ce on the sorbent Ce–Pd/ γ -Al2 O3 surface is 0.21% and 0.61%, which proved higher than that of the other three kinds of Pd-based sorbents, and observation from STEM-XEDS maps showed it demonstrated the highest dispersion. It is found that Ce is likely to promote the dispersion of Pd on the support surface during the preparation of the sorbent under the co-impregnation method. Meanwhile, Ce enhanced the H2 S resistance of the sorbent. Thereby, Ce–Pd/ γ -Al2 O3 sorbent is found to have the optimal performance of mercury removal. In this study, the Hg 0 removal mechanism of the Pd/Ce/ γ -Al2 O3 sorbents in the simulated coal derived fuel gas was also elaborated. Graphical abstract: Image 1 Highlights: Metal element impregnation sequence greatly influenced the performance of sorbent. Efficiency of Ce–Pd/ γ -Al2 O3 is higher and more stable than other three sorbents. Pd of Ce–Pd/ γ -Al2 O3 surface distributed more uniform than other three sorbents.